Bio-Organic Fertilizer: A Green Technology to Reduce Synthetic N and P Fertilizer for Rice Production - Umme Aminun Naher; Jatish Chandra Biswas; Md. Maniruzzaman; Faruk Hossain Khan; Md. Imran Ullah Sarkar; Afsana Jahan; Md. Hasibur Rahaman Hera; Md. Belal Hossain; Aminul Islam; Md. Rafiqul Islam; Md. Shahjahan Kabir (Frontiers in Plant Science, 2021)
Decomposed organic materials, in combination with plant growth-promoting bacteria (PGPB), are environmentally friendly and reduce synthetic fertilizer use in rice production. A bio-organic fertilizer (BoF) was prepared using kitchen waste (79%), chita-dhan (unfilled rice grain) biochar (15%), rock phosphate (5%), and a consortium of 10 PGPB (1%) to supplement 30% nitrogen and to replace triple superphosphate (TSP) fertilizer in rice production with an improvement of soil health. PGPB were local isolates and identified using 16S ribosomal RNA partial gene sequences as Bacillus mycoides, Proteus sp., Bacillus cereus, Bacillus subtilis, Bacillus pumilus, Paenibacillus polymyxa, and Paenibacillus spp. Isolates could fix N2 by 0.7–1.4 g kg–1, solubilize 0.1–1.2 g kg–1 phosphate, and produce 0.1–40 g kg–1 indoleacetic acid. The performance of BoF was evaluated by 16 field experiments and 18 farmers’ field demonstration trials during the year 2017–2020 in different parts of Bangladesh. Performances of BoF were evaluated based on control (T1), full synthetic fertilizer dose of N, P, and K (T2), BoF (2 t ha–1) + 70% N as urea + 100% K as muriate of potash (T3), 70% N as urea + 100% P as TSP + 100% K as muriate of potash (T4), and 2 t ha–1 BoF (T5) treatments. At the research station, average grain yield improved by 10–13% in T3 compared with T2 treatment. Depending on seasons, higher agronomic N use efficiency (19–30%), physiological N use efficiency (8–18%), partial factor productivity (PFP)N (114–150%), recovery efficiency (RE)N (3–31%), N harvest index (HIN) (14–24%), agronomic P use efficiency (22–25%), partial factor productivity of P (9–12%), AREP (15–23%), and HIP (3–6%) were obtained in T3 compared with T2 treatment. Research results were reflected in farmers’ field, and significant (P < 0.05) higher plant height, tiller, panicle, grain yield, partial factor productivity of N and P were obtained in the same treatment. Application of BoF improved soil organic carbon by 6–13%, along with an increased number of PGPB as compared with full synthetic fertilizer dose. In conclusion, tested BoF can be considered as a green technology to reduce 30% synthetic N and 100% TSP requirements in rice production with improved soil health.